2013
DOI: 10.1063/1.4829064
|View full text |Cite
|
Sign up to set email alerts
|

Wake-up effects in Si-doped hafnium oxide ferroelectric thin films

Abstract: Hafnium oxide based ferroelectric thin films have shown potential as a promising alternative material for non-volatile memory applications. This work reports the switching stability of a Si-doped HfO2 film under bipolar pulsed-field operation. High field cycling causes a "wake-up" in virgin "pinched" polarization hysteresis loops, demonstrated by an enhancement in remanent polarization and a shift of negative coercive voltage. The rate of wake-up is accelerated by either reducing the frequency or increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
265
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(278 citation statements)
references
References 21 publications
8
265
4
1
Order By: Relevance
“…8 We observed that a definite amount of wake-up cycles is required to enhance the hysteresis and P r as well as E C in these films. Our results were found to be in agreement with the previously published reports by Zhou et al 13 in ALD deposited Si-doped HfO 2 thin films and later on by Starschich et al 11 in chemical solution deposited Y-doped HfO 2 thin films, where the "wake-up" effect in the polarization hysteresis was observed. The "wake-up" (deaging) effect corresponds to an increase in the remnant polarization caused by the application of subsequent bipolar voltage cycles.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…8 We observed that a definite amount of wake-up cycles is required to enhance the hysteresis and P r as well as E C in these films. Our results were found to be in agreement with the previously published reports by Zhou et al 13 in ALD deposited Si-doped HfO 2 thin films and later on by Starschich et al 11 in chemical solution deposited Y-doped HfO 2 thin films, where the "wake-up" effect in the polarization hysteresis was observed. The "wake-up" (deaging) effect corresponds to an increase in the remnant polarization caused by the application of subsequent bipolar voltage cycles.…”
Section: Methodssupporting
confidence: 83%
“…17 These charged defects near the electrode/ferroelectric interface inhibit the growth of domains of opposite polarity. 13 High interfacial charged defects can lead to the band banding with the formation of a depletion layer where the built-in electric field (E bi ) across the depletion region can be expected to result in local alignment of ferroelectric dipoles. 2 Further, successive bipolar voltage cycles can cause removal or redistribution of these charged defects, which reduces the E bi by de-pinning more and more domains to participate in polarization switching.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this connection, anisotropic stresses are required for the phase transition from tetragonal to orthorhombic, i.e., a compressive stress within the aob plane and a tensile stress along the c-axis exerted on the t-phase. There are many factors reported hitherto to be responsible for causing the anisotropic stresses and thus stabilizing the ferroelectric o-phase during the film growth, such as doping, 4,5,[23][24][25][26][27][28][29][30][31][32][33][34][35] surface energy effect, [36][37][38] island coalescence, 39 thermal expansion mismatch, 17 capping layer effect, 4,38 and formation of oxygen vacancies. 40 The following of this section will discuss each of these factors in order.…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
“…2,3 Cathodoluminescence due to oxygen vacancies was also recently found in ion beam sputtered HfO 2 and first steps toward fabrications of hafnia micro-light emitting devices were already taken. 4,5 The resistance switching behavior due to formation and rupture of conductive paths within HfO 2 deposited by atomic layer deposition was exploited for random access memory fabrication.…”
mentioning
confidence: 99%